The Relevance of Amenities and Agglomeration for Dutch Housing Prices - Harry Garretsen; Gerard Marlet (European Regional Science Association (ERSA), 2011)
In this paper we have combined concepts from the field of urban economics with views from the area of geographic economics (the New Economic Geography). This approach enabled us to depict both the significance of the characteristics of the city itself and that of its location. Cities which combine a favourable location in terms of distance to work with a variety of urban amenities appear to be the most attractive locations for people to live. These are relatively safe cities, offering a variety of history and culture events, as well as good restaurants. In addition, successful cities are places where people can optimize their career prospects, not necessarily - as often assumed - as a result of business districts in these cities, but access to jobs from these cities.
Keywords: 330